Habitual abortion. Psychogenic factor. - Benavente Lozada, Benjamin (2015)
The importance of psychosomatic disorders in the etiology of habitual abortion has been highlighted by several authors. Tupper and Well, in a detailed study of personality and careful control of recurrent abortion patients, they conclude that psychological factors play a decisive role in triggering abortion. Psychological assistance in these patients throughout pregnancy resulted in a success of 84% compared to 26% of the group of untreated control.